Pengaruh Store Layout, Interior Display dan Human terhadap Shopping Orientation - Ainil Mardiah; Susi Evanita; Whyosi Septrizola (Journal of Management and Business Review, 2021)
Shopping orientation is defined as a form of interest attached to the individual and then provides motivation in making a purchase of a product. Shopping orientation has an attachment to social relationships because it involves how consumers reflect consumer conditions in the shopping environment. The purpose of this study was to determine the effect of store layout, interior appearance, and people on shopping orientation at Matahari Basko Grand Mall Padang. In general, the results of this study indicate that: store layout has a significant effect on shopping orientation at Matahari Basko Grand Mall, interior appearance has a significant effect on Shopping Orientation at Matahari Basko Grand Mall. Meanwhile, humans have no significant effect on Matahari Basko Grand Mall Shopping Orientation